Midpregnancy Cervical Length in Nulliparous Women and its Association with Postterm Delivery and Intrapartum Cesarean Delivery - van der Ven, A. J.; van Os, M. A.; Kleinrouweler, C. E.; Verhoeven, C. J. M.; de Miranda, E.; Bossuyt, P. M.; de Groot, C. J. M.; Haak, M. C.; Pajkrt, E.; Mol, B. W. J.; Kazemier, B. M. (American Journal of Perinatology, 2016)
Objective To evaluate the association between midpregnancy cervical length and postterm delivery and cesarean delivery during labor.Study Design In a multicenter cohort study, cervical length was measured in low-risk singleton pregnancies between 16 and 22 weeks of gestation. From this cohort, we identified nulliparous women who delivered beyond 34 weeks and calculated cervical length quartiles. We performed logistic regression to compare the risk of postterm delivery and intrapartum cesarean delivery to cervical length quartiles, using the lowest quartile as a reference. We adjusted for induction of labor, maternal age, ethnicity, cephalic position, preexisting hypertension, and gestational age at delivery.Results We studied 5,321 nulliparous women. Women with cervical length in the 3rd and 4th quartile were more likely to deliver at 42+0 to 42+6 weeks (adjusted odds ratio [aOR] 2.02, 95% confidence interval [CI] 1.07–3.79 and aOR 1.97, 95% CI 1.06–3.67, respectively). The frequency of intrapartum cesarean delivery increased with cervical length quartile from 9.4% in the 1st to 14.9% in the 4th quartile (p = 0.01). This increase was only present in intrapartum cesarean delivery because of failure to progress and not because of fetal distress.Conclusion The longer the cervix at midtrimester the higher the risk of both postterm delivery and intrapartum cesarean delivery.
Keywords: cervical length; postterm delivery; cesarean section; cohort study